An evaluation of the delivery of the Eskom Customer Safety Education Programme in the Queenstown Customer Services Area. - Mtyalela, Kanyisa Highly (Rhodes University, Faculty of Commerce, Rhodes Business School, 2014)
The aim of this research is to evaluate the Eskom customer safety education programme in the Queenstown Customer Services Area. The research focuses on the implementation of the programme with the aim of assessing whether there is need for optimisation in the way that the customer education and training is delivered. The paper consists of three sections. Section one is directed to Eskom and is made up of (i) a review of the literature that is relevant to the Eskom safety education programme, (ii) the findings made from the study and (iii) recommendations from the author. Section two is a review of the key concepts which were identified for this paper and these are: (i) education and training, (ii) consumer education, (iii) citizenship education, (iv) training programme development, and (v) training programme evaluation. Section three provides detail on and justifies the research methodology that was followed for this paper. The author adopted the deductive approach and collected data from literature sources and Eskom documents as well as face-to-face interviews with the Eskom trainers and customers. Qualitative data was collected from the interviews and is presented in section one of the report in the form of (i) narratives, (ii) graphs and (iii) tables. The research has identified some shortcomings in the delivery of the training and recommendations have been made on how these shortcomings can be addressed. Trainer skills, training evaluation and training tools are amongst the issues that require attention in the Queenstown Customer Services Area. The results revealed that 67 percent of the trainers have not received training related to conducting customer forums. Inconsistencies with regard to the evaluation of the training interventions were also identified and there were differences in terms of the training tools that are utilised at the forums. The recommendations made by the author are based on the literature that was reviewed as part of this study and are aimed at addressing the delivery of the training. The respondents all displayed an understanding of the objectives of the Eskom safety education programme and made recommendations in terms of how Eskom can reduce the tampering of Eskom equipment. The recommendations made included the involvement of the community as well as unannounced door-to-door audits aimed at identifying damaged and tampered Eskom equipment. These recommendations are in line with the guiding principles of safety education presented in McWhirter (2008: 32) which include the involvement of young people in real decisions to help them stay safe, as well as the use of active approaches in addressing safety issues. A review of the electrical contact incidents which were reported to Eskom in 2011/12 revealed that in 61,5 percent of the cases that occurred in the Eastern Cape, Eskom had conducted electricity safety education before the incidents occurred. The recommendations in terms of the training delivery should be implemented to improve the delivery of the training. The author however recommends further research on how Eskom can reduce the number of electrical contact incidents that occur, as it has been proven through previous studies that safety education "has an impact on knowledge, behaviour, risk and skills and no papers have provided evidence of the impact of safety education on injury rates" (Mulvaney, Watson and Errington, 2012: 27).
Keywords: Eskom (Firm); Customer relations -- Management; Safety education -- South Africa -- Queenstown; Safety education -- Evaluation; Safety consultants -- Rating of -- South Africa -- Queenstown; Public safety -- South Africa -- Queenstown